(untitled) (AmS-Skrifter, 2020)
The Hanseatic Kontor in Bergen was one of the main hubs of trade in the North Sea region. This paper explores a possibility suggested in a late sixteenth-century manuscript that the Norwegian Kontor for some time was also located at Notau, a place south of Bergen. It is argued that this written source might refer to the years 1427–33 when the Hanseatic merchants withdrew from Bergen because of an on-going war between King Erik and northern German princes. Notau is mentioned several times in sources from the fifteenth century and most of these references are related to Hanseatic activity. However, viewed in a broader context, Notau stands out as an important harbour on the south-western Norwegian coast, visited both by Norwegians and Hanseatics, as well as travellers from other regions.